The Influence of Vocational High School Students Communication with Parents, Teachers, and Peers on the Career Maturity (Jurnal Komunikasi Pembangunan, 2022)
Preparing future career includes developmental tasks for vocational students. This study aimed to describe the career maturity of vocational students and  analyze the influence of vocational students communication with parents, teachers and peers on their career maturity. We had 84 vocational students as sample in XII grade from four SMK in Kabupaten Tanngerang (2 private dan 2 public). We used data of career maturity inventory (CMI) Form C, which were analyzed using descriptive statistics. Data of the communication were analyzed using Smart PLS 3.0. The results showed that (1) the career maturity of vocational students 59,52% were in the medium category, 29,79% were in the low category, and 10,71% at the high category. This rate is caused by low self-confidence and students are still confused in making choices Beside that, female students have a higher career maturity rate than male students (2) there was a significant influence between vocational students communication   with teachers on career maturity, but there was no significant influence between vocational students communication with parents and peers on career maturity. This showed that communication interventions with career guidance service and counseling by teachers at the school can increase the career maturity of students.